Fenomena Banyak Anak di Kalangan Warga Pondok Pesantren Imam Bukhari - Saepudin, Ade (Lembaga Yasin AlSys, 2024)
This research examines the phenomenon of families with many children at the Imam Bukhari Islamic Boarding School in Surakarta, Indonesia. The concept of a family with many children is understood in the context of Salafi religious teachings and is applied by Salafi preachers, with reference to certain Fiqh books. This research is field research which uses qualitative descriptive research methods with an ethnographic approach. Ethnography is research that describes the culture of a community or society. Data sources in this research are divided into two types, namely field data (field research) as primary data and library data (library research) as secondary data. The research highlights the important role of economic, historical, sociological, religious and cultural factors in managing big families. In conclusion, the phenomenon of families with many children at the Imam Bukhari Islamic Boarding School can be explained through historical, religious and social factors involving key figures, religious teachings and interactions within the Islamic boarding school community.